Present Bias and Underinvestment in Education? Long-run Effects of Childhood Exposure to Booms in Colombia - Bladimir Carrillo (Fondazione Eni Enrico Mattei (FEEM), 2019)
This paper examines the long-run impacts of income shocks by exploiting variation in coffee cultivation patterns within Colombia and world coffee prices during cohorts' school-going years in a differences-in-differences framework. The results indicate that cohorts who faced higher returns to coffee-related work during school-going years completed fewer years of schooling and have lower income in adulthood. These findings suggest that leaving school during temporary booms results in a significant loss of long-term income. This is consistent with the possibility that students may ignore or heavily discount the future consequences of dropout decisions when faced with immediate income gains.
Keywords: J24; O12; O13; 330; Information Avoidance; Energy Efficiency; Moral Wiggle Roo